2018
DOI: 10.5176/2345-7198_5.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Foot Care Knowledge and Behaviors of Individuals with Diabetes Mellitus in Indonesia

Abstract: The most common diabetes mellitus (DM) complication is diabetic foot ulcer (DFU), which is costly and has devastating adverse effects. It was found that 6.8 % of DM patients suffered from DFU. According to Indonesian Hospital Association, DFU was reported to cause an amputation rate of 15-30 %. The aims of this study were to assess the levels of diabetic foot care knowledge and behaviors and its relationship among diabetic patients attending Public Health Center at Bojonegoro, East Java, Indonesia. Eighty-one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
2
1
0
1
Order By: Relevance
“…The current study revealed the difference between the scores of the diet and foot care awareness domains and their corresponding practices indicating that being knowledgeable does not guarantee sound practices, but there is always a need to motivate for sound practices supporting again the need for communitybased interventions. The low level of foot care practice domain agrees with other recent studies [44].…”
Section: Discussionsupporting
confidence: 92%
“…The current study revealed the difference between the scores of the diet and foot care awareness domains and their corresponding practices indicating that being knowledgeable does not guarantee sound practices, but there is always a need to motivate for sound practices supporting again the need for communitybased interventions. The low level of foot care practice domain agrees with other recent studies [44].…”
Section: Discussionsupporting
confidence: 92%
“…Considering the maximum and minimum scores obtainable on those scales, it can be said that the diabetic foot knowledge and self-care behaviors of the persons with T2DM were below the medium level. There are similar results in the literature (Azmi et al, 2020; Bekele & Berhanu, 2021; Gökdeniz & Akgün Şahin, 2022; Pourkazemi et al, 2020; Sulistyo et al, 2018). In one scoping review, 58 studies on determining diabetic foot care knowledge and its implementation in persons with DM, it was reported that there were differences in the levels of foot care knowledge and implementation in persons with DM (Manickum et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…Those questionnaires measured the knowledge and practices of patients with and without DFUs. Study of the Magbanua ( 17 ), Sari ( 33 ) and Sulistyo ( 31 ) were using illustrations that accompanied the questions to help participants understand the questions. Most the studies use their own national language in order to simplify the purpose of questions.…”
Section: Resultsmentioning
confidence: 99%